A eficácia do fortalecimento muscular dos abdutores e rotadores laterais do quadril associado aos músculos do joelho, em indivíduos sedentários com síndrome da dor femoropatelar: uma revisão sistemática - Pinto, João Paulo Silva (2021)
Objective: To review and systematize studies on the effectiveness of hip abductor (ABDT) and hip lateral rotator (RL) muscle strengthening (FTM) protocols associated with knee muscle FTM, given to the FTM protocols of the knee or hip muscles, in sedentary nodes comments (SDFP). Method: The following databases were searched: Pubmed; Cochrane Central Register of Controlled Trials; Sciverse Scopus and Physiotherapy Evidence Databases (PEDro), using the following keywords: [(patellofemoral pain syndrome OR patellofemoral pain OR patellofemoral OR anterior knee pain syndrome OR anterior knee pain syndromes OR patellofemoral pain syndromes) AND (training of resistance OR strength training OR muscle strengthening OR muscle strengthening OR strengthening OR) AND (randomized clinical trials OR clinical trials OR randomized controlled trials OR controlled clinical trials)]. Two researchers, independently and blindly, selected the studies based on the inclusion and exclusion criteria and how disagreements between them were resolved by a third party evaluated. The electronic and manual search selected: 499 published articles. Study quality and reporting quality were taken using a study quality assessment and exercise reporting tool (TESTEX), and after screening, only 10 studies were selected. Inter-rater agreement was performed, for each point on the TESTEX scale (15 in total), choosing, using the Kappa coefficient (K), proposed by Cohen, based on the following formula: K = (PO - PC) / (1 - PC), where PO is the number of agreements observed and PC is the number of agreements expected, by chance. Data were propagated in the Statistical Package for Social Science (SPSS - 23.0), after checking for normality (Shapiro test Wilk ), considering a significance level of P ≤ 0.05. Results: After evaluating the methodological quality, Conbrach's Alpha was performed to analyze the agreement between the evaluators' scores, thus obtaining an ICC = 0.917 (P <0.001) for study quality, an ICC = 0.804 (P < 0.012) for the study report and an ICC = 0.965 (P <0.001) in the total score, showing, in all obstacle domains, almost perfect agreement between the 2 raters. The 10 articles selected by each of the 2 evaluators obtained 1 to 4 points for study quality (maximum score = 5 points), and 5 to 10 points for the study report (maximum score = 10 points), reaching a maximum total score of 14 points, out of a possible score of 15 in the sum of the two domains (study and report), with mean values for assessed 1 and 2: 10.2 and 10.5 respectively. Conclusion: The FTM of the hip abductors (ABDT) and lateral rotators (RL) associated with the FTM of the knee muscles or strengthening of the hip muscles (abductors and lateral rotators) in isolation was more effective in decreasing pain and improving pain. knee function when compared to protocols that used only knee exercises in relation to sedentary patients with PFPS.